Rancang Bangun Aplikasi Simpan Pinjam Uang Mahasiswa Fakultas Teknik Universitas Asahan Berbasis Web - Helmi Fauzi Siregar; Nilfa Sari (Universitas Asahan, 2018)
Abstract - Savings and loan money is one of human needs. Where savings and loans are something that is very necessary to support the development of economic activities and improve living standards. In universities, there are many students who spend money to pay for their tuition fees. Among these students, there are fairly poor people. The author took the initiative to make a savings and loan application that is useful for students, if they need funds to complete lecture administration at any time. Students can also set aside a portion of their allowance to be stored in the application. In this way, students can reduce the burden a bit regarding the problems of lecture administration. Based on the description above, the author raised the research title with research conducted directly on the students of the Asahan University Faculty of Engineering with the title